El cine como recurso didáctico para el desarrollo de competencias éticas y emocionales = Abweichender Titel: Cinema as a Didactic Resourse for the Development of Ethical and Emotional Competencies - Hernández-Ramos, Juan Pablo (Cauriensia, 2025)
Among the competencies present in training curricula, emotional education, grounded in ethical principles, is considered relevant for addressing social challenges. This work aims to analyze and assess, from the perspective of teachers and students, the development of an innovative teaching experience in which, through the use of cinema, the goal is to establish and consolidate appropriate ethical principles and values for future education professionals. A convergent mixed-methods approach was used to develop an evaluative study with a single-group pre-experimental design. The study involved 6 teachers and 278 students. After watching the film, The Wave and completing a reflection activity, the students rated the experience positively. The results show that the activity allowed for the development of critical thinking, a better understanding of theoretical concepts, their application to real-life situations, and the expression of personal opinions. The paper concludes by emphasizing the importance of grounding the emotional education of education professionals in correct values, for both their personal and professional lives.